SARS-CoV-2 seroprevalence in Mongolia: Results from a national population survey - Battogtokh Chimeddorj; Undram Mandakh; Linh-Vi Le; Batzorig Bayartsogt; Zolzaya Deleg; Oyunsuren Enebish; Oyunbaatar Altanbayar; Battur Magvan; Anuujin Gantumur; Otgonjargal Byambaa; Gerelmaa Enebish; Bat-Erdene Saindoo; et al. (Elsevier, 2021)
Background: With the global spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in early 2020, Mongolia implemented rapid emergency measures and did not report local transmission until November 2020. We conducted a national seroprevalence survey to monitor the burden of SARS-CoV-2 in Mongolia in the months surrounding the first local transmission. Methods: During October-December 2020, participants were randomly selected using age stratification and invited for interviews and blood samples at local primary health centres. We screened for total SARS-CoV-2 antibodies, followed by two-step quantitative SARS-CoV-2 IgG serology tests for positive samples. Weighted and test-adjusted seroprevalences were estimated. We used chi-square, Fisher's exact and other tests to identify variables associated with seropositivity. Findings: A total of 5000 subjects were enrolled. We detected SARS-CoV-2 IgG antibodies in 72 samples. Crude seroprevalence of SARS-CoV-2 antibodies was 1•44% (95%CI,1•21-1•67). Population weighted and test-adjusted seroprevalences were 1•36% (95%CI,1•11-1•63) and 1•45% (95%CI,1•11-1•63), respectively. Age, sex, geographical, and occupational factors were not associated with seropositivity (p>0•05). Symptoms and signs within past 3 months and seropositivity were not associated at the time of the survey (p>0•05). Interpretation: SARS-CoV-2 seroprevalence in Mongolia was low in the first year of the pandemic potentially due to strong public health measures, including border restrictions, educational facilities closure, earlier adoption of mask-wearing and others. Our findings suggest large-scale community transmission could not have occurred up to November 2020 in Mongolia. Additional serosurveys are needed to monitor the local pandemic dynamic and estimate how far from herd immunity Mongolia will be following-up with vaccination programme in 2021 and 2022. Funding: World Health Organisation, WHO UNITY Studies initiative, with funding by the COVID-19 Solidarity Response Fund and the German Federal Ministry of Health (BMG) COVID-19 Research and development. Translation: Cyrillic and Traditional Mongolian translation of abstract is available on appendix section.